Developmental and reproductive toxicology : - Hood, Ronald D. (Taylor & Francis, 2006)
Originally titled Handbook of Developmental Toxicology, Developmental and Reproductive Toxicology: A Practical Approach, Second Edition is a guide for developmental and reproductive toxicologists. Completely revised and updated, new chapters cover genomics/preteomics, endocrine disruptors, testing for male reproductive toxicity, and testing for female reproductive toxicity. It covers evaluating and interpreting data. Both practical and informative, the book bridges the gap between theory and application. It contains insights gained from hands-on experience and gathers information scattered throughout the literature into one reference.